2014
DOI: 10.1039/c4nr04151h
|View full text |Cite
|
Sign up to set email alerts
|

Metallic nanowire networks: effects of thermal annealing on electrical resistance

Abstract: a Metallic nanowire networks have huge potential in devices requiring transparent electrodes. This article describes how the electrical resistance of metal nanowire networks evolve under thermal annealing.Understanding the behavior of such films is crucial for the optimization of transparent electrodes which find many applications. An in-depth investigation of silver nanowire networks under different annealing conditions provides a case study demonstrating that several mechanisms, namely local sintering and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
311
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(337 citation statements)
references
References 48 publications
26
311
0
Order By: Relevance
“…Some studies demonstrated the modification of electrode materials with ultrathin metal nanowires matrix [12][13][14]. However, highly reproducible devices with regard to the number of NWs crossing the contact electrode gap and contact areas between the NWs and contact electrodes [6,15] have not been practicable thus far. There are reports on low sensitivity, poor performance, and deviations in the cyclic voltammetry (CV) of low-dimensional electrodes [16,17], where the electrode dimension approaches the mean free pathway of the electron in the metal, approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies demonstrated the modification of electrode materials with ultrathin metal nanowires matrix [12][13][14]. However, highly reproducible devices with regard to the number of NWs crossing the contact electrode gap and contact areas between the NWs and contact electrodes [6,15] have not been practicable thus far. There are reports on low sensitivity, poor performance, and deviations in the cyclic voltammetry (CV) of low-dimensional electrodes [16,17], where the electrode dimension approaches the mean free pathway of the electron in the metal, approx.…”
Section: Introductionmentioning
confidence: 99%
“…However, our case appears significantly different because the uncompensated nanowire resistance in the present study resulted in the gradient of the potential along the NW. Consequently, it is difficult to introduce a defined value of this parameter over the length of the nanowire network electrode, because it depends on the distance from the contact point to the NWs from the external circuitry and on a percolation pathway [15], so that various points on the NW network Therefore, we would like to emphasize here that a more detailed study, e.g., with the variation of scan rate or concentration of the redox probes for quantitative interpretation of the data is hardly possible in this case. Furthermore, actual magnitudes are given rather for qualitative estimation, because the networks are unstable even in a narrow potential window and are intrinsically not reproducible.…”
mentioning
confidence: 99%
“…The immersion treatment in water leads to an efficient dissolution of the insulating capping agent PVP and thus results in a decrease in resistance, in accordance with the literature. Subsequent annealing at 150 ∘ C, the commonly reported glass transition temperature of PVP, aids to lower the resistance further by melting residual PVP and sintering the wire-to-wire junctions, which in turn increases the cross section of the wire-to-wire contact areas [55]. The effect of the water treatment is further studied by FTIR measurements, as shown in Figure 6(d) that depicts the spectra before and after immersion in water.…”
Section: Fabrication Of Transparent Conducting Films and Posttreatmentsmentioning
confidence: 99%
“…Due to the electrically insulating capping agent and solvent, that is, EG and PVP, the as-synthesized nanowires show a high resistance and cannot be used for most applications. Thus, a pre-or postdeposition treatment has to be applied [55]. As a predeposition treatment, the as-synthesized wires are usually centrifuged 1-3 times in acetone and subsequently in either ethanol or water to remove EG and PVP [6,33,42].…”
Section: Fabrication Of Transparent Conducting Films and Posttreatmentsmentioning
confidence: 99%
“…[120] Moreover, the percolated network structures maintain their conductive path by structural reconfiguration during mechanical deformation. Low fabrication cost is another advantage due to a solution-based processing that is compatible with roll to roll slot-die coating.…”
Section: Metal Nw-based Stecmentioning
confidence: 99%